Study of the intention of banana growers in improving the production in Jeli, Kelantan - Ahmad Firdaus Ibrahim (2016)
Banana cultivation had become the second ranked in terms of production area and fourth in export revenue based on the balance of trade ﬁgures. It is also the second most widely cultivated fruit. Thus, a survey of 70 farmer respondents was conducted in the district of Jeli, Kelantan area to determine knowledge, attitude and practices of farmer towards their banana cultivation. The data were then analyzed by using the chi-square test to see the relationship between farmer attitude and their practices on the farm. The chi-square test was also conducted to test the relationship between farmer practices and their banana cultivation productivity. All of chi-square test shown signiﬁcant results. Factor analysis was done to determine the inclination factor. The ﬁnding suggested that farmer practice was the ﬁrst factor that will inﬂuence banana cultivation productivity. Then, followed by attitude and knowledge. The study, therefore recommended that the farmer practices should be improvised and guidance are essential in order to achieve target demand by 2020.